Optimization of HVAC system energy consumption in a building using artificial neural network and multi-objective genetic algorithm - Nasruddin; Sholahudin; Satrio P.; Mahlia T.M.I.; Giannetti N.; Saito K. (Elsevier Ltd, 2023)
Air conditioning; Buildings; Cooling systems; Decision making; Energy conservation; Energy utilization; Genetic algorithms; Multiobjective optimization; Neural networks; Thermal comfort; Annual energy consumption; Building energy consumption; Building parameters; Dedicated outdoor air systems; Multi-objective genetic algorithm; Objective functions; Passive solar design; Radiant cooling; HVAC; air conditioning; artificial neural network; building; cooling; energy use; genetic algorithm; optimization; temperature effect